MANAJEMEN BIMBINGAN DAN KONSELING PADA SMP NEGERI 1 ANGKINANG KABUPATEN HULU SUNGAI SELATAN - Abidarda, Yulizar (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2018)
Guidance and Counseling aims to help improve the quality of students, assuming to improve the quality of graduation, both in quality and quantity. Management in this study covers activities: planning (planing), organizing (organizing), preparation of personnel (stafing), direction and leadership (leading) and supervision (controling).The method used in this study is a qualitative descriptive method. A qualitative approach is a research process and understanding that is based on methodologies that investigate social phenomena and human problems.The results of the study were Factual Guidance Management and Counseling Conditions Based on Interviews with Principals: Guidance Program Planning and Counseling Organizing Guidance and Counseling Programs, Preparation of Guidance and Counseling, Guidance and Leadership Guidance and Angkinang Counseling, Supervision and evaluation of Guidance and Counseling Evaluation in Public Middle Schools 1 Angkinang Factual Condition of Guidance and Counseling Management Based on Interviews with Guidance Guidance and Planning Counseling Guidance and Counseling Program Organizing Guidance and Counseling in Obstacles in organizing guidance and counseling, Guidance Preparation Guidance and Guidance and Guidance Counseling and Counseling Guidance Evaluation and Counseling Evaluation in Middle School Negeri 1 AngkinangConclusions in the study: Guidance and counseling planning was made at the beginning of the school year, involving all authorized staff, organizing Guidance and Counseling in its management effectively, arranging guidance and counseling personnel carried out alternately in accordance with the capabilities of the person. by the principal, where supervision is carried out by the principal and special supervisor of the education office with provisions that are adjusted to their needs, and assessment of guidance and counseling in accordance with the performance carried out by the supervising teacher, if the performance is good.